Evaluation of encapsulated astaxanthin from white shrimp shells (Litopenaeus vannamei) on hepatotoxicity - Niracha Yanyium; Wanida Sukketsiri; Pennapa Chonpathompikunlert; Wanwimol Klaypradit; Jirawat Saetan; Marais, Sebastien; Supita Tanasawet (Penerbit Universiti Kebangsaan Malaysia, 2024)
Recent advances in astaxanthin encapsulation have been reported, but hepatotoxic effect remains unclear. The present investigation therefore aimed to examine the effects of encapsulated astaxanthin from white shrimp shells (Litopenaeus vannamei) on liver toxicity. Wistar rats were divided into 6 groups as control (C), and receiving vitamin E (VE), astaxanthin commercial (AC), astaxanthin extracted from white shrimp shells (AE), astaxanthin encapsulation into powder form (AP), and blank powder (BP). The evaluation of liver in response to astaxanthin administration was then assessed in terms of biochemical parameters and histopathological features. Liver enzymes, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), showed no significant differences among all groups of treatment. Histopathological study showed no abnormal changes on liver tissue including hepatic inflammation. Our data demonstrated that astaxanthin encapsulation did not increase the expression of NF-ҡB nuclear translocation and CYP2E1 in comparison with the control group. Additionally, in this study, the consumption of astaxanthin and vitamin E resulted in a reduction in the oxidative stress index (OSI), while the levels of antioxidant enzymes, including glutathione peroxidase (GPx) and superoxide dismutase (SOD), were significantly increased compared to the control group. Our data suggested that astaxanthin encapsulation does not cause hepatic toxicity, contributing useful information in the applications of astaxanthin encapsulation technology.